Refreshing Kader Posyandu Bayi dan Balita sebagai Upaya Peningkatan Pengetahuan dan Keterampilan di Puskesmas Tirto - Swasti Artanti; Ni'matul Ulya (LPPM Akbid Harapan Ibu Pekalongan, 2023)
Puskesmas is the spearhead of public health services which is very important because it improves the degree of public health. One of the efforts to accelerate the reduction of maternal and infant mortality rates is implemented in the Posyandu (Integrated Service Post) program. Posyandu is one of the platforms that can be used to prevent and overcome health problems in nutrition, maternal and child health, clean and healthy lifestyles, immunization and so on. Health cadres who are around the community must have a high level of knowledge about health that occurs in the community. The purpose of this community service is as a means of updating health knowledge, especially regarding maternal and infant health with a target number of 25 cadre participants. This activity was carried out with a pre test, material provision, discussion and post test. From this activity it can be seen that there are 17 cadres who are well informed from the previous only 10 people. The author hopes that the government through the Puskesmas can conduct continuous coaching and refreshing cadres.